Cardiac autonomic modulation during progressive upper limb exercise by patients with coronary artery disease - Machado,H.G. (2011)
The purpose of this study was to investigate the behavior of heart rate (HR) and HR variability (HRV) during different loads of resistance exercise (incline bench press) in patients with coronary artery disease (CAD) and healthy sedentary controls. Ten healthy men (65 ± 1.2 years, control group, CG) and 10 men with clinically stable CAD (66 ± 2.4 years, CADG) were recruited. A discontinuous progressive protocol was applied with an initial load of 10% of the maximum load achieved in the 1RM (1 repetition maximum) with increases of 10% until 30% 1RM was reached, which was followed by subsequent increases of 5% 1RM until exhaustion. HRV was analyzed by linear and non-linear methods. There was a significant reduction in rMSSD (CG: 20 ± 2 to 11 ± 3 ms; CADG: 19 ± 3 to 9 ± 1 ms) and SD1 indexes (CG: 14 ± 2 to 8 ± 1 ms; CADG: 14 ± 2 to 7 ± 1 ms). An increase in HR (CG: 69 ± 5 to 90 ± 5 bpm; CADG: 62 ± 4 to 75 ± 4 bpm) and in systolic blood pressure (CG: 124 ± 3 to 138 ± 3 mmHg; CADG: 122 ± 6 to 126 ± 9 bpm) were observed (P < 0.05) when comparing pre-effort rest and 40% 1RM in both groups. Furthermore, an increase in RMSM index was also observed (CG: 28 ± 3 to 45 ± 9 ms; CADG: 22 ± 2 to 79 ± 33 ms), with higher values in CADG. We conclude that loads up to 30% 1RM during incline bench press result in depressed vagal modulation in both groups, although only stable CAD patients presented sympathetic overactivity at 20% 1RM upper limb exercise.